APPLICATION OF SIMULATION FOR MANUFACTURING SYSTEM MANAGEMENT - A CASE STUDY - Singhania, Rishi H.; Bilolikar, Vijay S. (Journal of Strategic Innovation and Sustainability, 2017)
The paper presents operating strategies for manufacturing systems using simulation. An existing manufacturing facility plagued with productivity issues is replicated in a virtual environment using Arena Simulation software. The analysis of the system is performed by varying input parameters such as Batch Size, Target Stock Level and Reorder Point of Inventory. The impact of the changes in the input parameters on the system evaluation parameters such as System Output, Resource Utilization, Inventory Status and Bottleneck Operations are studied. New strategies are hence developed and suggested to improve the performance of the plant.